1999
DOI: 10.1103/physrevlett.83.1771
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Coherence Resonance Oscillators

Abstract: The effect of coherence resonance can change the firing process in noise-driven excitable systems towards rather regular dynamics. For such stochastic oscillators, we study the synchronization in terms of locking of the peak frequencies in the power spectrum and also in terms of phase locking. Our investigations are based on numerical simulations of coupled Morris-Lecar neuron models and on fullscale experiments with coupled monovibrator electronic circuits. PACS numbers: 05.45.Xt, 05.40.Ca, 84.30.Ng, 87.17.Nn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
2
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 21 publications
1
58
2
9
Order By: Relevance
“…With this unified perspective we highlight the specificities of these phenomenologies in relation to other celebrated noise-constructive effects, typical of either forced or autonomous extended systems, i.e., array enhanced stochastic resonance [11,12], taming spatiotemporal chaos with disorder [13], noise-enhanced signal propagation [14,15], and noise-induced synchronization to global oscillations for arrays of excitable units [16,17] or coherence resonance oscillators [18,19]. Experiments were carried out using thin (0.3 mm), squared (3 3 3 cm 2 ) film of silica gel, in which the light-sensitive catalyst, ruthenium-bipyridyl [Ru(bpy)], was immobilized [9] [solution of 15% sodium silicate, 1.5 mM Ru͑bpy͒ 21 3 and 1M H 2 SO 4 ] prepared as in Ref.…”
mentioning
confidence: 99%
“…With this unified perspective we highlight the specificities of these phenomenologies in relation to other celebrated noise-constructive effects, typical of either forced or autonomous extended systems, i.e., array enhanced stochastic resonance [11,12], taming spatiotemporal chaos with disorder [13], noise-enhanced signal propagation [14,15], and noise-induced synchronization to global oscillations for arrays of excitable units [16,17] or coherence resonance oscillators [18,19]. Experiments were carried out using thin (0.3 mm), squared (3 3 3 cm 2 ) film of silica gel, in which the light-sensitive catalyst, ruthenium-bipyridyl [Ru(bpy)], was immobilized [9] [solution of 15% sodium silicate, 1.5 mM Ru͑bpy͒ 21 3 and 1M H 2 SO 4 ] prepared as in Ref.…”
mentioning
confidence: 99%
“…The most closely related are those by Han et al ͑1999͒, using monovibrator electronic circuits, who reported a small-͑spatial͒ scale realization of stochastic coherence with a pair of identical "stochastic" oscillators. With similar equipment, the same authors detected more recently noise-induced multimode FIG.…”
Section: Stochastic Coherence In Extended Mediamentioning
confidence: 99%
“…Theoretical [36][37][38][39][40][41][42] and experimental [43][44][45] works on coherence resonance addressed excitable dynamical systems that typically generate bursting time series. In such a system, there is usually a reference or a "silent" state, e.g., a fixed point, near which a trajectory can spend long stretches of time.…”
Section: Stochastic Driving Forcementioning
confidence: 99%
“…Quantitatively, associated with coherence resonance, the temporal regularity of the system dynamics depends on the noise amplitude and it can be maximized by noise of optimal amplitude. There were extensive studies of coherence resonance in the past decades both theoretically [36][37][38][39][40][41][42] and experimentally [43][44][45]. For low-dimensional chaotic systems, coherence resonance has also been studied [33,34,[46][47][48].…”
Section: Introductionmentioning
confidence: 99%